Gambaran Penyimpanan Obat di Rumah Sakit Umum Daerah Hajjah Andi Depu Kabupaten Polewali Mandar - Dini Nurdwiyanti, Puspa; Mursyid, A.Mumtihanah; Purnamasari, Vina (PHARMACY UMI JOURNAL SYSTEM, 2024)
Drug storage is an important stage in the drug management because proper drug storage can maintain drug quality, prevent irresponsible drug use, prevent theft and facilitate drug search and control in hospitals. The impact of the storage process that is not in accordance with pharmaceutical requirements is that the availability of drugs is not maintained and there is the potential for irresponsible drug use resulting in losses for the Hospital. The purpose of this study was to find out an overview of drug storage at the Hajjah Andi Depu General Hospital, Polewali Mandar Regency. This study used a descriptive method by comparing observational data, interviews and document searches with the Minister of Health Regulation Number 72 of 2016, Guidelines for Pharmaceutical Supplies Management in Hospitals 2010, and Technical Guidelines for Pharmaceutical Service Standards in Hospitals 2019. The data obtained will be calculated based on the guttman scale, then calculate the percentage value of compliance with the regulations. Based on the results of the study it can be seen that the drug storage process at the Hajjah Andi Depu Regional General Hospital, Polewali Mandar Regency, is in the very good category with the acquisition of a conformity percentage value of 82.76%.